ANALISIS PERSEPSI KONSUMEN TERHADAP FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN PEMBELIAN KERIPIK NANGKA UMKM DAPUR SIMBOK - Adila Putri Marela; Luhur Aditya Prayudhi; Tri Kurniastuti; Rima Dewi Oryza Sativa (Universitas Tribhuwana Tunggadewi, 2025)
This study aims to analyze the influence of price perception, packaging, and taste on purchasing decisions for jackfruit chips at Dapur SiMbok, a Micro, Small, and Medium Enterprise (MSME) in Blitar Regency, Indonesia. Employing a quantitative descriptive approach with 68 respondents selected through purposive sampling, data were collected via questionnaires and analyzed using multiple linear regression. The findings reveal that simultaneously, all three variables significantly influence purchasing decisions (F = 38.196; sig. 0.000). Partially, price (t = 4.267; sig. 0.000), packaging (t = 3.522; sig. 0.001), and taste (t = 5.665; sig. 0.000) each exert a positive and significant effect. Taste emerges as the dominant factor (? = 0.475), surpassing price (? = 0.345) and packaging (? = 0.281). This research offers practical implications for snack MSMEs, encouraging them to prioritize taste innovation as a core marketing strategy.